Efektivitas Implementasi Bimbingan Kelompok Dengan Teknik Modeling Untuk Meningkatkan Self Confidence Pada Siswa SMP - Ni Wayan Yuni Arshita Ni Wayan Yuni Arshita; Nyoman Dantes Nyoman Dantes; Kadek Suranata Kadek Suranata (SCHOULID: Indonesian Journal of School Counseling, 2023)
This research aims to describe Self Confidence tendencies in students and the effectiveness of implementing group guidance using modeling techniques to increase Self Confidence in students. This research is a type of quantitative research using an experimental approach with a One Group Pre-test, Post-test Design. The population used was 404 class VII students at SMP Negeri 1 Singaraja. The sampling technique used a purposive sampling technique so that 1 class was selected, namely class VII A3, totaling 37 students with an average age of 13 - 14 years, then took 12 students from the pretest results whose students' self-confidence was the lowest to be given group guidance services. modeling techniques. The data collection method uses observation, a questionnaire regarding Self Confidence with 30 statement items and documentation. The prerequisite test methods used are the normality test of data distribution and the homogeneity test of group variance. The data description method used is theoretical ideal reference assessment (PAIT). Hypothesis testing uses Paired Sample T-Test and the Effect Size is also calculated using Cohen's formula. The results of data analysis show that the Sig (2-tailed) value is <0.001, so H0 is rejected and Ha is accepted. And the result of the Effect Size calculation is 3.991 with a strong effectiveness category. So it can be concluded that modeling technique group guidance is effective in increasing students' Self Confidence.